Mycorrhizal colonization and phenolic compounds accumulation on roots of Eucalyptus dunnii maiden inoculated with ectomycorrhizal fungi - EDUARDO LUIZ VOIGT; VETÚRIA LOPES DE OLIVEIRA; ÁUREA MARIA RANDI (Pesquisa Agropecuária Brasileira, 2000)
Compatibility between Eucalyptus dunnii and the ectomycorrhizal fungi Hysterangium gardneri and Pisolithus sp. - from Eucalyptus spp. -, Rhizopogon nigrescens and Suillus cothurnatus - from Pinus spp.-, was studied in vitro. Pisolithus sp., H. gardneri and S. cothurnatus colonized the roots. Pisolithus sp. mycorrhizas presented mantle and Hartig net, while H. gardneri and S. cothurnatus mycorrhizas presented only mantle. S. cothurnatus increased phenolics level on roots. Pisolithus sp. and R. nigrescens decreased the level of these substances. The isolates from Eucalyptus seem to be more compatible towards E. dunnii than those from Pinus. The mechanisms involved could be related, at least in the cases of Pisolithus and Suillus, to the concentration of phenolics in roots.